Unlocking Efficiency: A Holistic Examination of Freight Forwarder Evaluation through Analytical Hierarchy Process (AHP) at PT XYZ - Aggasi, Sania; Ulfah, Mutia (Journal of Applied Business Administration, 2024)
This study undertakes an evaluation of five freight forwarders in PT XYZ with the objective of mitigating customer complaints pertaining to delivery delays, incorrect deliveries, and damaged goods during transit. Employing the Vendor Performance Indicator (VPI) criteria framework, comprising quality, cost, delivery, flexibility, and responsiveness, alongside the Analytical Hierarchy Process (AHP) method, data was collected through questionnaires distributed to three stakeholders within the customs and transportation department. The analysis identifies responsiveness as the most critical criterion, followed by delivery accuracy and cost considerations. Within these criteria, the ability to respond to customer demands, accuracy of material delivery, and shipping costs are delineated as the most influential sub-criteria. Forwarder MD is identified as the top performer, with forwarder CV and forwarder BI following closely. The findings reveal that forwarder MD emerges as the optimal long-term partner for PT XYZ. These findings offer actionable insights and a clear recommendation for PT XYZ or other companies facing similar challenges in selecting the most suitable freight forwarder thus can empower them to make strategic decisions, ultimately driving improvements in service delivery, customer satisfaction, and operational effectiveness on their business.